Synchronization of Making Limited Liability Company Deeds by Notaries Based on the Law on Notary Positions Integrated With Online Single Submission System as a Business Facility (A Study in Banda Aceh City) - M. Raja Aqsa Mufti; Azhari Yahya; Teuku Abdurrahman (International Journal Reglement & Society (IJRS), 2022)
In managing Limited Liability Company (PT) files, the government has used an Online Single Submission (OSS)-based system. Not all business actors understand the OSS system so that they authorize a Notary to manage the company files. The authority granted through the power of attorney is deemed inappropriate and is not regulated in the Law on Notary Positions (UUJN). This study aims to explain the authority of a Notary as a power of attorney in carrying out the making of a Limited Liability Company deed that is synchronized with the Online Single Submission/OSS, setting up a business license through an electronically integrated business licensing service (Online Single Submission/OSS) and the legal consequences of making a limited liability company deed that is not synchronized with the Online Single Submission (OSS) system in the Banda Aceh City area. The results of the study indicate that the Notary's Authority as a Power of Attorney in Implementing the Making of Limited Liability Company Deeds Synchronized With Online Single Submission / OSS is not regulated in the Notary Position Act (UUJN), but in practice the community, especially business actors, gives power to the Notary as a party who take care of the Online Single Submission filing in order to avoid mistakes that occur when uploading files so that it can cause losses for the business actors themselves. Setting up a Business License through the OSS Electronically Integrated Business Licensing Service is that by logging into the OSS system, Business Actor is required to create a User-ID to log-in and fill in data to obtain a Business Identification Number (NIB) as the identity number of a Business Actor issued by Online Single Submission agency. The Business Identification Number (NIB) also applies as a Company Registration Certificate (TDP), the legal consequences of making a Limited Liability Company Deed that are not synchronized with the Online Single Submission System (OSS) is that if the deed is made not in accordance with the 2020 KBLI then OSS will reject the file submission automatically, when making the articles of association for the first time, it is to remind Business Actor regarding the latest systems